Реінкарнація пам'яті, або Портрет покоління в інтер'єрі часу: "Діти Чумацького Шляху" Докії Гуменної - Василенко, В.С. (Слово і Час, 2019)
У статті проаналізовано роман-тетралогію “Діти Чумацького Шляху” Докії Гуменної в контексті
художньої прози української діаспори повоєнного часу. Досліджено жанрову природу, позицію
наратора, проблеми взаємозв'язку часу та простору. З'ясовано, що визначальною в романі є ідея
поколіннєвої свідомості, а поняття покоління пов'язано з категоріями роду, пам'яті, ідентичності
(національної, соціальної, культурної, ґендерної). Крім того, порушено питання про наявність
у романі альтернативних автобіографій письменниці як одного зі способів конструювання
самоідентичності. The paper analyzes the tetralogy of novels by Dokiia Humenna “Children of the Milky Way” in the
context of the postwar Ukrainian diaspora fiction. The researcher raises such issues as the genre
nature, narrator’s position, problem of the relationship between the categories of time and space, and
the alternative autobiography of the novel.
The process of writing the novel is considered as an attempt to normalize the writer’s own traumatic
experience, caused by two decades of totalitarian terror and repressions.
Dokiia Humenna’s novel is regarded in the context of such genres as family chronicle and ‘novel
of generations’, which was updated in Ukrainian literature of the post-war period as an attempt to
overcome the threatening tendencies of the entropy. At the same time, considering the fact that the
novel was written on the verge of fiction and documentaries, the researcher suggested reviewing the
work in the context of testimonial literature. It is emphasized that ideas of generational consciousness
and generational dimension of time shape the novel, and the concept of generation is associated with
categories of ancestry, memory, trauma, and identity. The generation of Ukrainian 1920s, which Dokiia
Humenna considers as her own, emerges in the novel as a complex and heterogeneous socio-cultural
phenomenon, represented by historical figures that became symbols and signs of their time (Mykola
Khvylovyi, Mykola Zerov, and others), by literary stories of their alter ego, and fictional characters,
sometimes based on several real prototypes.
The myth of primordialism is one of the most important in the novel. It is represented by the archetype
of a hamlet, a patriarchal micromodel of Ukraine, traditional in classical Ukrainian literature.
In addition, the author of the paper raised a question about the presence of the writer’s alternative
autobiographies in the novel, which might be the ways of constructing her own identity.